2013
DOI: 10.1073/pnas.1302855110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of brain networks in the aesthetic appreciation

Abstract: Neuroimage experiments have been essential for identifying active brain networks. During cognitive tasks as in, e.g., aesthetic appreciation, such networks include regions that belong to the default mode network (DMN). Theoretically, DMN activity should be interrupted during cognitive tasks demanding attention, as is the case for aesthetic appreciation. Analyzing the functional connectivity dynamics along three temporal windows and two conditions, beautiful and not beautiful stimuli, here we report experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 70 publications
5
114
0
2
Order By: Relevance
“…However, the emotional arousal associated with these predictions, we think, is generated by the interactions with the striatal dopaminergic system. This framework, and others like it (124), could also be thought of more broadly as applicable to other types of aesthetic rewards: for example, some authors have suggested that visual aesthetic experiences may arise from interactions across cortical regions involved in perception and memory (125); also, Cela-Conde et al (126) emphasize synchronization across cortical fields as important for visual aesthetics.…”
Section: Putting It All Togethermentioning
confidence: 99%
“…However, the emotional arousal associated with these predictions, we think, is generated by the interactions with the striatal dopaminergic system. This framework, and others like it (124), could also be thought of more broadly as applicable to other types of aesthetic rewards: for example, some authors have suggested that visual aesthetic experiences may arise from interactions across cortical regions involved in perception and memory (125); also, Cela-Conde et al (126) emphasize synchronization across cortical fields as important for visual aesthetics.…”
Section: Putting It All Togethermentioning
confidence: 99%
“…This ongoing engagement with space differs from our engagement with art. Investigators have probed early and a slightly later response to artwork, but such research is still confined to experiences that last less than a few seconds in duration (Cela-Conde et al, 2013). There is recognition that aesthetic experiences vary over longer durations than a few seconds (Chatterjee, 2014;Leder & Nadal, 2014), although the average museum patron spends less than 20 sec engaging with works of art (Smith, Smith, & Tinio, 2017;Smith & Smith, 2001).…”
Section: Measurement Challengesmentioning
confidence: 99%
“…Finally, by analyzing the dynamics of brain functional connectivity, Camilo Cela-Conde et al (19) offer the first identification of brain networks engaged within distinct time frames during the appreciation of beauty. A fast aesthetic perception of the beautiful/notbeautiful condition of each visual stimulus appears within 250-750 ms whereas further aesthetic appreciation processes are subsequently performed in the 1,000-to 1,500-ms range.…”
Section: Human Difference: From Ethics To Aestheticsmentioning
confidence: 99%